PATOLOGI BIROKRASI DALAM PELAYANAN PUBLIK Studi Pelayanan Administrasi Kependudukan di Kantor Kecamatan Pucuk Kabupaten lamongan - Midkholus Surur; Yendra Erison; Alif Firdaus Zam Zam; Mahmud Aprian Mabruri; Ferdi Edreyan Indra Wanto (Universitas Islam Darul Ulum Lamongan, 2023)
Bureaucracy is an important instrument in society whose presence is inevitable. Bureaucracy is a logical consequence of the acceptance of the hypothesis that the State has a sacred mission, namely to prosper its people. The purpose of this research is to find out the forms of bureaucratic pathology and efforts to overcome bureaucratic pathology in population administration services at the Pucuk District Office. This research uses a qualitative approach with a case study strategy. This research uses a case in Pucuk Subdistrict, Lamongan Regency, to explore the forms of bureaucratic pathology and efforts to overcome them. In this case study, informants were determined using purposive sampling technique. The data collected was analyzed through a process of data reduction, data presentation, conclusion drawing and verification. As for the results of research and data analysis conducted by researchers, in Public Services at the Pucuk District Office, Lamongan Regency is running well. This can be seen from the implementation process which is in accordance with the principles of good governance that must be applied, such as community participation in various sub-district activity programs. The form of transparency provided is also quite good and effective, such as providing the widest possible information about public services both through sheets of paper and through media such as the internet. Accountability provided to the community is also quite good even though it has not been implemented optimally, such as the lack of funds in the implementation of various activities.